ChemInform Abstract: Ruthenium(II)‐Catalyzed Functionalization of C—H Bonds via a Six‐Membered Cyclometallate: Monoarylation of Aryl 2‐Pyridyl Ketones. Issue 30 (29th July 2014) - Li, Bin; Darcel, Christophe; Dixneuf, Pierre H.
Abstract In most reactions small amounts of bisarylated byproducts are found which are readily removed by column chromatography.